Permafrost Active Layer Microbes From Ny Ålesund, Svalbard (79°N) Show Autotrophic and Heterotrophic Metabolisms With Diverse Carbon-Degrading Enzymes - Sipes, Katie; Paul, Raegan; Fine, Aubrey; Li, Peibo; Liang, Renxing; Boike, Julia; Onstott, Tullis C.; Vishnivetskaya, Tatiana A.; Schaeffer, Sean; Lloyd, Karen G. (Frontiers in Microbiology, 2022)
The active layer of permafrost in Ny Ålesund, Svalbard (79°N), is increasing in thickness at a rate of ~one vertical centimeter per year in most locations around the Bayelva River in the Leirhaugen glacier moraine. In other permafrost soils, microbes in the active layers have been shown to drive organic matter degradation and greenhouse gas production, creating a positive feedback on climate change. However, the microbial metabolisms relating the environmental geochemical processes and the populations that perform them have not been fully characterized. In this paper, we present geochemical, enzymatic, and isotopic data paired with ten novel Pseudomonas sp. cultures and metagenomic libraries of two active layer soil cores (BPF1 and BPF2) from Ny Ålesund, Svalbard, (79°N). Isotopic signatures between the two study sites indicate that the dominant microbial metabolism is heterotrophy in BPF1 and autotrophy in BPF2, since C/N, organic carbon content, and POXC values indicate that BPF1 has more labile carbon than BPF2. Further, xylosidase and N-acetyl--D-glucosaminidase show enzymatic activity that is cold-adapted in the cultures and bulk soil. The high activity for leucine aminopeptidase across soils and cultures corresponds to organisms using leucine as a nitrogen and carbon source in energy limited environments. This multifaceted approach suggests that the Svalbard active layer will be an expanding hotspot for microbial activity as the Arctic continues to warm.